Capital Capacity of The Logistics Industry For Investments Involving The Construction of Logistics Centres - Ilona DZIEDZIC-JAGOCKA; Dagmara MICHTA (Communications of International Proceedings, 2023)
In the economy there is a tendency to concentrate, a similar situation also occurs in the logistics sector, where there are more and more logistics centers. The role of logistics centers is to create additional value in the flow of goods, alleviating or eliminating the nuisance that logistics activities have on the environment, and supporting, and often initiate positive trends and directions of development of economic activities especially (but not only) in the area of logistics. In terms of closer economic realities logistics centers helping to increase the efficiency and effectiveness of logistics processes, customer service, creating value in the supply chain and reduction of logistics costs [Fechner, 2004].
Keywords: logistics centre; logistics; sources of funding